2020
DOI: 10.1016/j.bonr.2020.100711
|View full text |Cite
|
Sign up to set email alerts
|

Validation of HR-pQCT against micro-CT for morphometric and biomechanical analyses: A review

Abstract: High-resolution peripheral quantitative computed-tomography (HR-pQCT) has the potential to become a powerful clinical assessment and diagnostic tool. Given the recent improvements in image resolution, from 82 to 61 μm, this technology may be used to accurately quantify in vivo bone microarchitecture, a key biomarker of degenerative bone diseases. However, computational methods to assess bone microarchitecture were developed for micro computed tomography (micro-CT), a higher-resolution technology only available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Sp is usually defined as the distance between midlines of edges of trabeculae, providing important information about osteoporotic samples. [ 56 ] According to our previous observations, the value of Tb. Sp is positively associated with the degree of osteoporosis or osteolysis, which is characterized by aggravated inflammation and persistent bone infection.…”
Section: Resultsmentioning
confidence: 98%
“…Sp is usually defined as the distance between midlines of edges of trabeculae, providing important information about osteoporotic samples. [ 56 ] According to our previous observations, the value of Tb. Sp is positively associated with the degree of osteoporosis or osteolysis, which is characterized by aggravated inflammation and persistent bone infection.…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, a significant correlation was found between Ct.Th and BV/TV, especially between the iliac crest and the radius in our study. A review evaluating the validation of HR-pQCT against microCT reinforces the importance of matching anatomical sites when performing such comparisons ( Ohs et al, 2020 ). Maquer et al ( Maquer et al, 2015 ) evaluated radius, iliac crest, femur, and spine fragments by microtomography and observed that the iliac crest BV/TV was greater than the radius BV/TV, as seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it depends on expertise in execution, processing, and reading, which can be time consuming ( Moe et al, 2006 ; Dempster et al, 2013 ). MicroCT analyzes the microarchitecture in a three-dimensional manner, but it also requires an invasive biopsy and detects only the mineralized matrix ( Ohs et al, 2020 ). HR-pQCT has characteristics similar to those of microCT in terms of the method used (X-ray attenuation) and the analyzed parameters of microarchitecture in a three-dimensional manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, thresholds greater than 680 mg HA/cm 3 were ignored in the trabecular bone based on the lower mineralized density of trabecular bone and minimal trabecular bone volume measured at higher densities. A threshold of 320 mg HA/cm 3 was defined as a standardized threshold for analysis, based on the use as a trabecular threshold in previous studies 52 . The two images were then compared to determine voxels that had formed, resorbed, or were quiescent at each mineralized density threshold 53 .…”
Section: Methodsmentioning
confidence: 99%